2013
DOI: 10.1597/11-200
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Enamel Defects in Permanent Teeth of Patients with Complete Cleft Lip and Palate

Abstract: Objective : To evaluate the prevalence, types, location, and characteristics of enamel defects in anterior permanent teeth of patients with complete unilateral and bilateral cleft lip and palate, as well as the relation with the cleft. Setting : Hospital for Rehabilitation of Craniofacial Anomalies, Bauru, São Paulo, Brazil. Participants : Eighty patients of both genders, 12 years and older, with unilateral or bilateral cleft lip and palate. Methods : A single examiner carried out clinical examination under ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 27 publications
3
26
2
4
Order By: Relevance
“…The case group comprised 104 children with DDE and the control group was made up of 105 children without DDE, matched for gender and age. Children who did not cooperate during the exam and those with lip and/ or palate abnormalities 15 or systemic problems, such as asthma 16 and celiac disease, 17 which are associated with DDE, were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…The case group comprised 104 children with DDE and the control group was made up of 105 children without DDE, matched for gender and age. Children who did not cooperate during the exam and those with lip and/ or palate abnormalities 15 or systemic problems, such as asthma 16 and celiac disease, 17 which are associated with DDE, were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Clefts, cases in the sample having cleft lip history shows different degrees of enamel hypoplasia and hypocalcification this was assured by certain study (52) that found that there was a significant relationship was found between the cleft side and enamel defects, the highest prevalence on the cleft side suggests that the cleft does influence the occurrence of enamel defects in permanent teeth, this were in agreement with other studies (35,53) and more recently (54) where enamel defects was more common in CL(P) children in both primary and permanent dentition.…”
Section: Concerning Cases Of Previously Repairedmentioning
confidence: 92%
“…No data are available on the success rate of the OM and fluorescence‐based devices as diagnostic methods for DEDs, so we assumed that the diagnosis rate of these methods would be similar to that of conventional visual examination. Considering a DED prevalence rate of 92% the minimum number of dental surfaces required to detect a difference of 5% with a level of significance of 5%, a test power of 80% and design effect, was 198.…”
Section: Methodsmentioning
confidence: 99%